Thyrotoxic hypokalemic periodic paralysis due to Graves’ disease in 2 adolescents - Jung Gi Roh (Annals of Pediatric Endocrinology & Metabolism, 2019)
Thyrotoxic periodic paralysis (TPP) is a notable and potentially lethal complication of thyrotoxicosis, and Graves’ disease is the most common cause of TPP. TPP is commonly reported in Asian males between 20–40 years of age, but it is rare in children and adolescents. We report 2 Korean adolescents (a 16-year-old male and a 14-year-old female) with episodes of TPP who were previously diagnosed with Graves’ disease. These 2 patients presented with lower leg weakness in the morning after waking up. They were diagnosed with TPP-associated with thyrotoxicosis due to Graves’ disease. After they were initially treated with potassium chloride and antithyroid drugs, muscle paralysis improved and an euthyroid state without muscle paralytic events was maintained during follow-up. Therefore, clinicians should consider TPP when patients have sudden paralysis and thyrotoxic symptoms such as goiter, tachycardia, and hypertension.